2023
DOI: 10.37504/map.v6i1.507
|View full text |Cite
|
Sign up to set email alerts
|

Peran Pelatihan, Motivasi Dan Kompetensi Guru Terhadap Kinerja Guru Pada Madrasah Aliyah Negeri (Man) Sampang

Abstract: This study aims to analyze the role of training, motivation and teacher competence on teacher performance at the State Madrasah Aliyah (MAN) Sampang. This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 69 respondents. The results showed that both partially and simultaneously the training, motivation and competence of teachers partially affected the performance of teachers in the State Madrasah Aliyah (MAN) Sampang.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar research with different results was revealed by (Aisyah et al, 2022), revealing that partially training had no effect on teacher performance. (Anam & Winarko, 2023;Yulizar, 2019) expressed the same thing that training has a positive effect on teacher performance.…”
Section: Introductionmentioning
confidence: 99%
“…Similar research with different results was revealed by (Aisyah et al, 2022), revealing that partially training had no effect on teacher performance. (Anam & Winarko, 2023;Yulizar, 2019) expressed the same thing that training has a positive effect on teacher performance.…”
Section: Introductionmentioning
confidence: 99%